The influence of transformational leadership, compensation on task performance mediated by organizational commitment - Yuntina, Lily -; Sari, Eliana; Karnati, Neti (LPMPP Universitas Negeri Yogyakarta, 2025)
Task performance is a crucial component in the implementation of higher education and plays a significant role in enhancing education quality. This study aims to measure and analyse the relationship between transformational leadership, compensation, organisational commitment, and task performance. A mixed-methods approach with a causal model was employed. Primary data were collected through surveys, using a stratified random sampling method involving 250 permanent lecturers. Data were analysed using statistical techniques with the SmartPLS structural equation modelling software.. The results showed that 1) transformational leadership and compensation have a direct positive influence on task performance, accounting forup to 49%; 2) transformational leadership and compensation also have a direct positive influence on organizational commitment up to 21%; and 3)the study proposes a management model for improving lecturers' task performance, emphasizing the roles of transformational leadership, compensation, and organizational commitment in achieving organizational goals.